Controlled Delivery of MicroRNAs into Primary Cells Using Nanostraw Technology - Pop,MA; Almquist,BD (Advanced NanoBiomed Research, 2021)
MicroRNAs (miRNAs) are small noncoding RNAs that play key roles in posttranscriptional gene regulation. Being involved in regulating virtually all cellular processes, from proliferation and differentiation to migration and apoptosis, they have emerged as important epigenetic players. While most interest has gone into which miRNAs are involved in specific cellular processes or pathologies, the dosagedependent effects of miRNAs remain vastly unexplored. Different doses of miRNAs can cause selective downregulation of target genes, in turn determining what signaling pathways and cellular responses are triggered. To explore this behavior, the effects of incremental miRNA dosage need to be studied; however, current delivery methods for miRNAs are unable to control how much miRNA enters a cell. Herein, an approach is presented based on a nanostraw–electroporation delivery platform that decouples the delivery from biological mechanisms (e.g., endocytosis) to enable precise control over the amount of miRNA delivered, along with demonstrating ratiometric intracellular delivery into primary dermal fibroblasts for miR181a and miR27a. In addition, it is shown that the nanostraw delivery platform allows efficient delivery of miRNAs into primary keratinocytes, opening new opportunities for successful miRNA delivery into this hardtotransfect cell type.